Mniejszości narodowo-etniczne w rozszerzonej Unii Europejskiej - Filipek, Magdalena (National and Ethnical Minorities in Enlarged European Union, 2005)
By May 2004 Poland will have become a member of the European Union and national minorities living on the territory of Poland automatically will be an integral part of minority community in the European Union. It will certainly cause new problems. New phenomena will come out which we have not paid attention to so far. Therefore, now it is important to diagnose the scale of the phenomenon of national and ethnical minorities in the context of all European countries and to consider how the problem will be formed after the 1st May, 2004.For a few years Poland have been preparing to adapting legal rights to European standards. On the 1st April, 2001 Poland became a party of a general convention of the European Council about protection of national minorities. Not all of the principles contained in the convention have fully found reflection in the Polish legislation. The existing gap is to be bridged by the law about national and ethnical minorities in Poland prepared by the Polish Seym. Article 10.2 of the convention may be an example of such a legal blank which tells about possibility of using the language of national minorities before offices. There is no doubt that most of the rules written in the convention have been put into force in Poland. However, you should be conscious that the document also includes the principles which have not found enough reflection in the Polish legislation yet and those which need specifying or explaining. The fundamental problem is the fact that there is no legal certificate in which it would be specified which national and ethnical minorities live on the territory of Poland.Poland is only one of the countries which will be struggling every now and again with new ethnical matters within the next few years. Currently about 472 000 people live in Poland who are numbered among the minority population. It is a mere 1,23% of the whole population of Poland. However, in the context of joining the European Union Poland should aim that both national minorities living in Poland and the Poles living in European Countries have comparable minority laws guaranteed irrespective of which country they decided to settle.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 453-466